2014
DOI: 10.1039/c3ra42201a
|View full text |Cite
|
Sign up to set email alerts
|

β-Substituted γ-butyrolactams from mucochloric acid: synthesis of (±)-baclofen and other γ-aminobutyric acids and useful building blocks

Abstract: In the course of our exploration of the application of mucohalic acids in organic synthesis, we reported the synthesis of a,b-dihalo-a,b-unsaturated g-butyrolactams by reductive amination of a suitable mucohalic acid and a suitable amine. However, the functionalization of the aand/or b-halogen was found to be elusive under Suzuki conditions that worked well with the corresponding g-lactones. Although the corresponding b-aryl derivative was obtained under some of the modified Suzuki conditions tried, the yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…A suspension of carboxylic acid in toluene was heated to reflux for 5 h. After cooling to room temperature, the solvent was evaporated and the pure product was obtained. 1 H- and 13 C-NMR data for the compounds (±)- 2a – c [42], are identical with those described in the literature.…”
Section: Methodssupporting
confidence: 53%
“…A suspension of carboxylic acid in toluene was heated to reflux for 5 h. After cooling to room temperature, the solvent was evaporated and the pure product was obtained. 1 H- and 13 C-NMR data for the compounds (±)- 2a – c [42], are identical with those described in the literature.…”
Section: Methodssupporting
confidence: 53%
“…The work of Das Sarma et al reported the reductive amination of mucochloric acid derivative 2.11.h with NaBH-(OAc) 3 in 50% yield (Scheme 30). 60 It should be noted that the protocol leads to racemic baclofen 2.11. The RME of the reductive amination step was 23% (379 mg of the product).…”
Section: Baclofenmentioning
confidence: 99%
“…Lactam 6 can be easily transformed to N ‐substituted derivatives of 4‐hydroxy‐pyrrolidin‐2‐one. N ‐alkylation of lactam 6 by benzyl bromide furnished 8 with 82 % yield (Scheme ) . Subsequently, the dimethyl(phenyl)silyl group in 8 was converted to a hydroxy group (Scheme ) following the Tamao–Fleming oxidation with retention of configuration at C(4) chiral center and provided ( R )‐ N ‐benzyl‐4‐hydroxy‐pyrrolidin‐2‐one 9 which can be transformed to ( R )‐GABOB 10 , .…”
Section: Resultsmentioning
confidence: 99%